2019
DOI: 10.1111/maps.13262
|View full text |Cite
|
Sign up to set email alerts
|

Petrology and geochemistry of olivine‐phyric shergottites LAR 12095 and LAR 12240: Implications for their petrogenetic history on Mars

Abstract: Larkman Nunatak (LAR) 12095 and LAR 12240 are recent olivine‐phyric shergottite finds. We report the results of petrographic and chemical analyses of these two samples to understand their petrogenesis on Mars. Based on our analyses, we suggest that these samples are likely paired and are most similar to other depleted olivine‐phyric shergottites, particularly Dar al Gani (DaG) 476 and Sayh al Uhaymir (SaU) 005 (and samples paired with those). The olivine megacryst cores in LAR 12095 and LAR 12240 are not in eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 62 publications
(194 reference statements)
2
20
1
Order By: Relevance
“…Pyroxene Ti/Al can help to constrain a range of pressures of crystallization (not an exact pressure, as it is not fully calibrated for Mars; Filiberto et al., 2010; Nekvasil et al., 2007). The application of this geobarometer to various shergottites and chassignites suggests that formation of staging chambers at the crust/mantle boundary may be widespread on Mars, possibly leading to the formation of the various shergottite lithologies (Combs et al., 2019; Dunham et al., 2019; Filiberto 2017; Howarth et al., 2018; Nekvasil et al., 2004; Rahib et al., 2019; Udry et al., 2017). Minor element compositions in pyroxene in nakhlites also suggest that they could have formed at the bottom of the martian crust (McCubbin et al., 2013; Udry & Day, 2018).…”
Section: Igneous Emplacement Of Martian Magmasmentioning
confidence: 99%
See 2 more Smart Citations
“…Pyroxene Ti/Al can help to constrain a range of pressures of crystallization (not an exact pressure, as it is not fully calibrated for Mars; Filiberto et al., 2010; Nekvasil et al., 2007). The application of this geobarometer to various shergottites and chassignites suggests that formation of staging chambers at the crust/mantle boundary may be widespread on Mars, possibly leading to the formation of the various shergottite lithologies (Combs et al., 2019; Dunham et al., 2019; Filiberto 2017; Howarth et al., 2018; Nekvasil et al., 2004; Rahib et al., 2019; Udry et al., 2017). Minor element compositions in pyroxene in nakhlites also suggest that they could have formed at the bottom of the martian crust (McCubbin et al., 2013; Udry & Day, 2018).…”
Section: Igneous Emplacement Of Martian Magmasmentioning
confidence: 99%
“…First are the basaltic shergottites, which mostly contain pyroxene (average lengths of 0.3 mm, up to 1 mm) and maskelynite and are characterized by the absence of olivine phenocrysts or megacrysts (Figure 3a; e.g., He et al., 2015; Howarth et al., 2018; McSween et al., 1996; Rubin et al., 2000). Second in abundance are the olivine‐phyric shergottites, which are porphyritic and contain olivine phenocrysts (sometimes megacrystic with sizes up to 2.5 mm) with later‐crystallizing olivine, pyroxene, and maskelynite (Figure 3b; grains in the groundmass of ∼0.25 mm; e.g., Balta et al., 2015; Basu Sarbadhikari et al., 2009; Basu Sarbadhikari et al., 2016; Chen et al., 2015; Dunham et al., 2019; Goodrich, 2002; Liu et al. 2016a).…”
Section: A Variety Of Lithologies Representing Predominantly Igneous mentioning
confidence: 99%
See 1 more Smart Citation
“…LAR 12095 and LAR 12240 were recovered from the Larkman Nunataks region of the Transantarctic mountains, East Antarctica in 2012 (McBride et al 2013). They have been described in detail by several previous workers (Howarth et al 2014;Mikouchi and Takenouchi, 2014;Balta et al 2015a;Funk, 2015, Funk et al 2016Dunham et al 2019) suggesting that on the basis of petrography, mineral-chemistry and whole rock major and trace element geochemistry they are paired stones from the same meteorite fall (Dunham et al 2019). Both are olivine-pyhric shergottites containing olivine phenocrysts up to 3 mm in size, with rare pyroxene macrocrysts up to 2 mm in size.…”
Section: Lar 12095 and Lar 12240mentioning
confidence: 81%
“…Both are olivine-pyhric shergottites containing olivine phenocrysts up to 3 mm in size, with rare pyroxene macrocrysts up to 2 mm in size. Dunham et al (2019) characterized the modal mineralogy of LAR 12095/12240 and found the groundmass predominantly comprises olivine (~16-17 vol %), pyroxene (61)(62) vol %) and maskelynite (21-23 vol %). Minor phosphates, oxides (~1 vol %) and sulfides (~1 vol %) are also present.…”
Section: Lar 12095 and Lar 12240mentioning
confidence: 99%